Enhancing Aviation Software Development: An Experience Report on Conducting Audits - Marques, Johnny; Yelisetty, Sarasuaty; Slavov, Talita; Barros, Lilian (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2023)
Software audits have paramount importance as they play a critical role in upholding the integrity, security, safety, and regulatory compliance of software systems. In the context of aviation, the RTCA DO-178C standard is specifically designed to guide the development and certification of safety-critical software used in aircraft systems. The RTCA DO-178C standard is a crucial framework for ensuring that safety-critical software in aviation systems adheres to rigorous guidelines and objectives throughout the development process. These guidelines are indispensable in ensuring that the software fulfills the stringent safety requirements necessary for airworthiness certification. The primary objective of this report is to share the author’s extensive experience in conducting software audits onboard aircraft. Over the course of 20 years working in the industry, the authors have amassed valuable data from numerous audits. The findings encompass 4 distinct scenarios and 7 key pitfalls identified in 93 Planning Audits, 110 Development Audits, and 98 Verification Audits.